“La prescripción como modo de extinguir las obligaciones y su incidencia en el pagaré a la orden, en las sentencias de la Unidad Judicial Civil del cantón Riobamba, en el período enero – julio del 2016.” - Nogales Guerrero, Daniel Homar (2017)
In the present investigation, it will be indicated that the promissory note is an executive title, which in general terms the law grants certain principles such as authenticity, as well as immediate execution, which basically expresses an obligation and holds all the conditions to make it enforceable, for that reason the promissory note to the order is an immediate execution title. The promissory note for is part is constituted as one of the instruments most used to guarantee the obligations, in such a way that instrument has a practical importance that is based on the use of civil and commercial obligations. The executive title is a document whose essential characteristic is that it contains the condition of enforced execution of an obligation that has been stated in writing. Within the Ecuadorian legislation there is no conceptualization of what the executive titles are, nevertheless, it goes on to cite the referring norm. The purpose of the prescription is to acquire the extraneous things and to “extinguish the actions and rights of others”, which is the one to be analyzed in the present work, adjusting the prescription as a way to extinguish an executive title, since the law grants the Executive title shares and rights. As an observation regarding the prescription as way to extinguish an executive title, the Civil Code calls it “extinctive prescription “, which focuses on the prescription as a way to “extinguish”.